GEOMETRIC, VOLUMETRIC, COLOUR AND FRICTIONAL PROPERTIES OF SELECTED SALVIA SPECIES OF TURKEY - Bayram, Mustafa; Altuntas, Ebubekir; Yilar, Melih (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Salvia seeds are promite to dietary and healthy oils because they contain essential fatty acids. Salviaseeds frequently produce mucilage on soaking, and this mucilage is used for the treatment of eye diseases in easterncountries. Salvia species studied for medicine, food and cosmetics, have the potential to be used in the various fields.In the present study, selected engineering (geometrical, volumetrical, colour and frictional) properties of 6 Salviaspecies seeds were determined and compared.Materials and Methods: This study was performed on selected engineering properties of seeds of 6 Salvia species(Salvia viridis L., Salvia aethiopis L., Salvia cryptantha Montbert & Aucher ex Benthan., Salvia tomentosa Mill.,Salvia sclarea L., Salvia virgata Jacq.,) cultivated in Turkey. Plants were collected during the vegetation in 2012-2013(May-Agust). The seeds were cleaned from foreign matter, dirt and broken seeds manually.Results: The average length, width and thickness were found in the range of 2.61 to 3.53 mm, 1.59 to 2.92 mm and1.14 to 2.52 mm, respectively. Salvia viridis L. specie had the lowest geometric mean diameter and surface area,whereas Salvia cryptantha L. had the least values among these 6 Salvia species for these properties. The bulk density,true density and the porosity were between 296.83 and 702.80 kg m-3, 285.69 and 718.08 kg m-3, 10.27 and 44.05%,respectively. The volume of unit seed and sphericity ranged between 2.56 and 13.64 mm3, 62.90 and 90.40%,respectively. The coefficient of friction of salvia species were largely influenced by the friction surfaces studied, andhighest values were found for polywood in the Salvia crytantha L.. In the study, the static friction coefficient and theangle of repose of salvia species changed from 0.477 to 0.955, and from 14.09 to 23.57°, respectively.Conclusion: Determination of geometric, volumetric, colour and frictional properties of Salvia spp. seeds may increasetheir economic value.